Urban Movements and Climate Change Loss, Damage and Radical Adaptation - Armiero, Marco; Turhan, Ethemcan; de Rosa, Salvatore Paolo (Protest and Social Movements, 2023)
From the social uprisings in Santiago de Chile to the radical municipalism experiments in Naples, this volume takes the reader on an intellectual journey at the frontlines across global South and global North where climate breakdown meets social innovations. While the effects of the climate crisis are becoming more extreme and tangible across the globe with every passing day, urban social movements and their radical strategies to resist climate injustice often remain concealed from sight. Contributors to this volume ask how would it be to look at the politics of urban loss-and-damage not from the highly securitized zones of climate summits, but from favelas in Rio de Janeiro, flood-prone communities in São Paulo, urban gardens in Naples, or neighborhoods resisting climate gentrification in New York City? This book explores diverse worlds and praxis of urban social movements resisting the rising tides of climate crisis and social injustice.